2019
DOI: 10.1021/acschemneuro.9b00468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Multifunctional Ligand for Simultaneous Inhibition of Amyloid-Beta (Aβ42) and Chelation of Zinc Metal Ion

Abstract: Zinc binding to β-amyloid structure could promote amyloid-β aggregation, as well as reactive oxygen species (ROS) production, as suggested in many experimental and theoretical studies. Therefore, the introduction of multifunctional drugs capable of chelating zinc metal ion and inhibiting Aβ aggregation is a promising strategy in the development of AD treatment. The present study has evaluated the efficacy of a new bifunctional peptide drug using molecular docking and molecular dynamics (MD) simulations. This d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…It is noteworthy that the DFT data is very consistent with the results of the BAR method in the present study. Also, compared to the results of our previous work done by the linear interaction energy (LIE) method, which has some underestimating error, the free energy calculated in this study is more consistent with experimental investigations and DFT …”
Section: Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is noteworthy that the DFT data is very consistent with the results of the BAR method in the present study. Also, compared to the results of our previous work done by the linear interaction energy (LIE) method, which has some underestimating error, the free energy calculated in this study is more consistent with experimental investigations and DFT …”
Section: Results and Discussionsupporting
confidence: 84%
“…Also, compared to the results of our previous work done by the linear interaction energy (LIE) method, which has some underestimating error, the free energy calculated in this study is more consistent with experimental investigations and DFT. 45 2.2. Peptide−Zn 2+ Interaction with Different Aβ Forms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co (II) [95,96], Pt (II) [97][98][99], Ru (II) [100,101], and heterometallic Pt(II)-Ru(II) [102] complexes proved effective too for this purpose, also through chelation of Cu (II) that was captured from Aβ [103]. It is thus not surprising that peptides binding Cu(II) [104][105][106][107][108][109][110], Zn(II) [111][112][113], and Cd(II) [112] have been successfully designed to inhibit Aβ fibrillation. Researchers have sought to combine gold NPs with Cu (II) chelating peptides to develop effective inhibitors (Figure 8) [114].…”
Section: Amyloid Beta (Aβ) Fibrillation Inhibitors Based On Metal-ion...mentioning
confidence: 99%
“…Although results are often contradictory, there is a general consensus that the Aβ/Cu 2+ complex formation drives and modulates the final end of the aggregation process. It was demonstrated that, depending on the protein/ion ratio, the aggregation is driven toward amorphous or fibrillar structures. , In the last decade, many peptide inhibitors of Aβ aggregation have been proposed and evaluated for the treatment of AD . Peptides capable of both preventing fibril formation and sequestering free Cu 2+ ion are particularly interesting. …”
Section: Introductionmentioning
confidence: 99%